A wave and finite element based homogenised model for predicting sound transmission through honeycomb panels. (22nd December 2019) - Yang, Yi; Mace, Brian R.; Kingan, Michael J.
Abstract: For vibroacoustic analysis, honeycomb-cored panels are often modelled as homogenised solid plates, which involves various assumptions and approximations. In this paper, a wave and finite element (WFE) based modelling strategy is proposed to predict sound transmission through honeycomb-cored panels. In this method, a three-dimensional periodic cell of the structure is modelled using a conventional finite element (FE) method. Due to the complexity of the core geometry, the FE model can contain a large number of internal nodes. Guyan reduction is used to reduce the model size. The in-vacuo wavenumbers are found, and from them the group velocities and modal densities determined. Wave propagation in the fluids surrounding the structure is modelled analytically. The acoustic loading is modelled using equivalent external nodal forces. The relatively small-sized mass and stiffness matrices are then post-processed using periodicity theory and equilibrium conditions. An accurate homogenised model is developed for calculating the structural response to acoustic excitation. Excitation of the structure by oblique plane waves and a diffuse sound field are both considered. Various numerical examples are presented to illustrate this model. The homogenised model developed in this paper is general and accurate, and can model sound transmission through honeycomb-cored panels of any configurations.